A checklist and host catalogue of the aphids (Hemiptera: Aphididae) held in the Australian National Insect Collection - Brumley, Cameron (Zootaxa, 2020)
The aim of this paper is to provide a checklist for Australian collected aphids present in the Australian National Insect Collection. Host plants for each species are provided, alongside Australian State and territory distribution. Six species are documented for the first time in Australia: Aphis forbesi, Micromyzella filicis, Trichosiphonaphis polygoni, Wahlgreniella nervata, Reticulaphis distylii and Reticulaphis inflata. A total of 137 new host plant associations are documented, spread across 51 species of aphids. A list of the remaining species previously published as present in Australia is also included.